Students' perceptions of teacher Strategies For Developing Speaking Skills Under The Merdeka Curriculum At The Eleven Grade Of SMA Yadika Bandar Lampung - Jeni Safitri; Dameria Magdalena Sidabalok (Cita konsultindo, 2024)
This research analyzes students' perceptions regarding the implementation of strategies for developing speaking skills through an Merdeka Curriculum in the eleventh grade at SMA Yadika Bandar Lampung using a qualitative approach. The aim of this research is to determine students' perceptions regarding the implementation of strategies to improve learning skills through the application of Merdeka learning at school. The research method used was a qualitative descriptive method with a population of 103 class XI students. Data will be collected through questionnaires and interviews. There are 3 strategies that will be studied, namely games, role play and group discussions. The goal that researchers want to achieve is to find out the effectiveness of each strategy implemented through student perceptions. Data analysis revealed that students had varying views about the effectiveness of the teaching strategies implemented by teachers. Although many of them admit the importance of this strategy in improving speaking abilities. Because this really affects the class atmosphere and students' confidence in speaking. This research concludes that most students think games can help them improve their speaking skills, starting from self-confidence, motivation, class atmosphere, mastery of material and other aspects of speaking. The implications of this research can help teachers and policy makers to develop more effective teaching strategies in facing the demands of the Merdeka Curriculum to develop students' speaking skills at SMA YADIKA BANDAR LAMPUNG.